(untitled) - Abdolrahman Ghateolbahr , Ehsan Mohammadinejad , Fazlollah Samimi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Nowadays, interpreting plays a very important role in communication, especially in political summits. Every single sentence uttered by political leaders might have a serious role in world peace. Moreover, these utterances could have effects on the lives of billions of people. This situation puts the interpreters under huge stress which can be seen in their performances. Research on this sort of interpreting which is called simultaneous interpreting is among rare works, which need more consideration. This study aimed to investigate political and cultural discourses as well as finding out the most frequent strategies adopted by a professional interpreter. The strategies adopted by the interpreter are applied to the speech of the president of the US, Donald Trump, who delivered at the United Nations on September 19th, 2017. The analysis of the speech showed the most frequent strategies are transcoding, omission, and message abandonment, which in some cases result in poor rendition. This study implies that interpreters become aware of the importance of cultural awareness in this task and how necessary it is to be ready to encounter cultural expressions and else.